Risk Control in Supply Chain Tobacco Processing Unit Using House of Risk Method (A Case of Indonesia) - Suryaningrat, Ida Bagus Bagus; Nurmalasari, Marsa Suci; Mahardika, Nidya Shara; Purnomo, Bambang Herry; Kuswardhani, Nita (International Journal on Food, Agriculture and Natural Resources, 2024)
There is a tobacco processing factory located in Maesan, Bondowoso, Indonesia that has been facing a problem of high demand but a lack of raw materials to meet it. Unfortunately, the demand for their product is decreasing every year. Therefore, the company needs to conduct a study of risk control within their supply network to identify potential risks and agents involved. The HOR method is employed to identify and analyze risks as well as the agents present within the supply chain of the tobacco processing facility. The company also needs strategies to manage the identified risks. The HOR method comprises two stages: the initial phase entails identifying risks and risk agents emerging within the factory's supply chain utilizing the Supply Chain Reference Operation (SCOR) approach. Phase two is the stage of determining the priority order of mitigation strategies that can be implemented at the factory. In the initial phase of HOR, 46 instances of risk events were identified within the supply chain, while the second phase involved selecting 27 risk agents for mitigation strategies. The results of phase two of HOR yielded 12 mitigation strategies that were implemented in the factory. These mitigation strategies were then ranked based on their ability to handle the existing risk agents.